Virtual Classroom Management: Planning, Implementation, and Evaluation in Online English Courses - Rohmah, Nafilatur; Zuhri, Moh. Shofi; Hidayati, Uji Nur (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2023)
English is a mandatory part of the education curriculum. However, English language learning is perceived to be less effective, prompting continued interest in additional courses, including online ones. Online class management in English courses presents both opportunities and challenges, requiring careful planning, organization, implementation, and supervision to achieve learning objectives. Field observations indicate various challenges in online english learning. Therefore, this research aims to describe the planning, implementation, and evaluation of online English learning at Bahasaku Inggris. This case study employs a qualitative descriptive approach. The result of this research reveals that lesson planning involves setting clear objectives, with participant analysis serving as a crucial source of information for planning. Lesson planning also requires the preparation of teaching materials, methods, and media such as images, videos, whiteboards, recorders, and assessment plans. Continuous evaluation is conducted through various means, including exams, assignments, and practical exercises, aiming to ensure constructive feedback and a holistic understanding of English by the students.